Lupin proteins: Structure, isolation and application. (October 2021) - Shrestha, Smriti; Hag, Leonie van 't; Haritos, Victoria S.; Dhital, Sushil
Abstract: Background: The interest in plant-based protein sources has risen in the last few decades due to their benefits to human health, the environment and sustainable farming. Lupins are a protein-rich legume crop, popular as fodder but limited for human consumption due to the presence of alkaloids. The sweet lupin varieties (free of/reduced alkaloid) developed through intensive plant breeding have widened the scope of lupin applications in food. Scope and approach: This review firstly compares the composition of the major globular proteins of Australian Sweet Lupin ( Lupinus angustifolius ) with soybean ( Glycine max ) followed by a review of the underlying principles of three well-established extraction methods: alkaline extraction-isoelectric precipitation; micellization; and selective fractionation, used for the preparation of lupin protein isolates (LPI). We have also discussed the functional properties of isolated proteins concerning the extraction methods. Key findings and conclusions: The extraction conditions, which mainly rely on pH change or salt concentrations, can be modified to achieve isolation of the desired protein fraction. We conclude that extraction conditions have a direct influence on various functional properties. LPI resulting from alkaline extraction-isoelectric precipitation led to protein denaturation due to acid treatment, while micellization produces LPI in a less denatured form resulting in better protein solubility, emulsifying and foaming properties. LPI from selective fractionation has the advantage of recovering γ-conglutin exhibiting good foaming capacity, whereas, alkaline extraction-dialysis/ultrafiltration recovered albumin along with globulin exhibiting excellent gelling behaviour. This review is timely for driving future research and applications in lupin seed as a sustainable, plant-based protein source for human foods. Highlights: Lupin globulin protein composition is compared with soy proteins. Extraction method influences functional properties of lupin protein isolates. Alkaline extraction-isoelectric precipitation delivers higher protein recovery. Micellization process yields superior quality lupin protein isolates in its native form.